Incentives and Student Learning: A Natural Experiment with Economics Problem Sets - Grove, Wayne A; Wasserman, Tim (American Economic Review, 2006)
Incentives and Student Learning: A Natural Experiment with Economics Problem Sets by Wayne A. Grove and Tim Wasserman. Published in volume 96, issue 2, pages 447-452 of American Economic Review, May 2006